Investigation of in-Service and Pre-Service Science Teachers’ Perceptions of Scientific Process Skills - YILDIRIM, MEHTAP (My University, 2020)
This study aims to determine the perceptions of the use of scientific process skills of in-service and pre-service teachers working in branches related to science courses in secondary and high schools. Therefore, this research was designed based on a relational survey model and was carried out with 150 science teachers in Turkey and 260 pre-service teachers from two different universities. The Scientific Process Skills Perception Scale was used to measure their perceptions of scientific process skills. An independent sample t-test was applied to compare the difference between the perceptions of scientific process skills of in-service and pre-service teachers. The results showed no significant difference between the two groups. The ANOVA results further showed that the duration of teachers’ service did not make a significant difference in their scientific process skill perceptions. The results of this study revealed that in-service and pre-service teachers should be supported with training to reduce their reservations about using scientific process skills. Keywords: Pre-service science teachers, Scientific process skills perception, Science teachers,